Extended release mixed amphetamine salts and topiramate for cocaine dependence: A randomized clinical replication trial with frequent users. (1st January 2020) - Levin, Frances R.; Mariani, John J.; Pavlicova, Martina; Choi, C. Jean; Mahony, Amy L.; Brooks, Daniel J.; Bisaga, Adam; Dakwar, Elias; Carpenter, Kenneth M.; Naqvi, Nasir; Nunes, Edward V.; Kampman, Kyle
Highlights: Participants met criteria for current cocaine use disorder. Participants required to report using cocaine more than 8 days in the prior month. Randomized to receive mixed amphetamine salts-ER and topiramate or placebo. The treatment group achieved higher rates of abstinence at the end of the study. Trial shows that this combined pharmacologic approach shows promise. Abstract: Background: Cocaine use disorder (CUD) remains a substantial public health problem with no clearly effective pharmacotherapy available. In a prior trial, combined amphetamine and topiramate treatment significantly reduced cocaine use among individuals demonstrating the most frequent use at baseline. This trial targeted such frequent users. Methods: A double-blind, randomized placebo-controlled trial, testing the combination of mixed amphetamine salts extended-release (MAS-ER) and topiramate or placebo over a 12-week medication phase was conducted. The two-site outpatient trial included 127 adults (96 males) with CUD using at least 9 days in the prior month. MAS-ER was titrated to a maximum dose of 60 mg/day and topiramate to a maximum dose of 100 mg twice/day. The primary outcome was the proportion of individuals who achieved three consecutive abstinent weeks at the end of the study (EOS) as measured by urine toxicology and self-report. Results: The proportion of participants achieving three abstinent weeks at the EOS was significantly ( P  = .03) larger in the treatment (14.1%) compared to the placebo group (0.0%), while controlling for baseline cocaine use, sex, current alcohol use disorder, and site. Of note, due to conservative cardiac safety-parameters a considerable number of individuals in the treatment group were discontinued from study medication (20.3%). Conclusions: While these findings provide further evidence that the combination of MAS-ER and topiramate is efficacious in promoting abstinence in CUD adults with frequent use it remains possible that the combination treatment is no more effective than either treatment alone. Despite this, the study provides a valuable "proof of concept."